Pola Komunikasi Keluarga dan Perilaku Merokok pada Remaja di Kecamatan Keera Kabupaten Wajo - Ikdafila Ikdafila; Besse Nurfadillah; Khaeriah B; Arni AR; Nirmawati Darwis; Fitriani Fitriani (Journal Research of Nursing & Midwifery (JRNM), 2026)
Adolescent smoking remains a major public health concern in Indonesia, including in Keera District, Wajo Regency. Smoking behavior among adolescents is influenced by various factors, one of which is family communication patterns. Ineffective family communication may weaken parental supervision and reduce openness between parents and adolescents, thereby increasing the risk of smoking behavior. This study aimed to examine the relationship between family communication patterns and smoking behavior among adolescents in Keera District, Wajo Regency. This study employed a quantitative analytical design with a cross-sectional approach. The study population consisted of 951 adolescents, and a sample of 90 respondents was selected using an accidental sampling technique. Data were collected using a structured questionnaire and analyzed using Spearman's rank correlation test. The results showed that the majority of respondents had poor family communication patterns (87.8%) and were classified as heavy smokers (55.6%). Spearman's rank correlation analysis revealed a statistically significant relationship between family communication patterns and adolescent smoking behavior (p = 0.035; r = −0.223). The negative correlation coefficient indicates that better family communication is associated with a lower likelihood of smoking among adolescents, although the strength of the relationship was weak. In conclusion, family communication patterns are significantly associated with smoking behavior among adolescents in Keera District, Wajo Regency. Strengthening open, supportive, and consistent family communication may serve as an effective strategy for preventing adolescent smoking, while also considering other contributing factors such as peer influence, the social environment, and media exposure.